IMPROVING STUDENTS VOCABULARY MASTERY THROUGH USING DIGITAL DICTIONARY AT 11TH GRADE OF SMK TEKNOLOGI NASIONAL BEKASI - Siti Fatimah; Subadar Subadar (Panca Sakti Bekasi : Jurnal Pendidikan dan Bisnis, 2022)
The purpose of this research was to improve students in grade 11th grade of Teknik Kendaraan Ringan (TKR) major at SMK Teknologi Nasional Bekasi mastery English learning with using daily vocabulary memorization media and a digital dictionary. Students were required to create a sentence using ten daily vocabulary words that they have memorized. The observation method was used to conduct this research, which was combined with a qualitative research design approach. The extent of students' English vocabulary mastery skills was determined through interview techniques. The problem that researchers found, is that students of 11th grade at SMK Teknologi Nasional Bekasi are still relatively poor at recognizing and mastering vocabulary. Mastery of English vocabulary among students is not up to 50%. Another problem found was that students have been unable to look up English vocabulary in printed dictionaries. Most students still make mistakes in the process to correctly using vocabulary, and there is still a lack of self-awareness and student motivation to learn English. The first factor is that most students still do not know how to use vocabulary and are too lazy to open a dictionary; the second factor is that students have difficulty determining appropriate vocabulary to communicate and write; and the third factor is that students' ability to remember and memorize vocabulary is still relatively low.